Differential Expression of Group I Metabotropic Glutamate Receptors in Functionally Distinct Hippocampal Interneurons - van Hooft, Johannes A. (J Neurosci, 2000)
Metabotropic glutamate receptors (mGluRs) have been proposed to be involved in oscillatory rhythmic activity in the hippocampus. However, the subtypes of mGluRs involved and their precise distribution in different populations of interneurons is unclear. In this study, we combined functional analysis of mGluR-mediated inward currents in CA1 oriens–alveus interneurons with anatomical and immunocytochemical identification of these interneurons and expression analysis of group I mGluR using single-cell reverse transcription-PCR (RT-PCR). Four major interneuron subtypes could be distinguished based on the mGluR-mediated inward current induced by the application of 100 μmtrans-(1S,3R)-1-aminocyclopentane-1,3-dicarboxylic acid (ACPD) under voltage-clamp conditions and the action potential firing pattern under current-clamp conditions. Type I interneurons responded with a large inward current of ∼224 pA, were positive for somatostatin, and the majority expressed both mGluR1 and mGluR5. Type II interneurons responded with an inward current of ∼80 pA, contained calbindin, and expressed mainly mGluR1. Type III interneurons responded with an inward current of ∼60 pA. These interneurons were fast-spiking, contained parvalbumin, and expressed mainly mGluR5. Type IV interneurons did not respond with an inward current upon application of ACPD, yet they expressed group I mGluRs. Activation of group I mGluRs under current-clamp conditions increased spike frequency and resulted in rhythmic firing activity in type I and II, but not in type III and IV, interneurons. RT-PCR results suggest that activation of mGluR1 in the subsets of GABAergic interneurons, classified here as type I and II, may play an important role in mediating synchronous activity.